2017
DOI: 10.1016/j.immuni.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Loop Involving IL-6 Family Member LIF, LIF Receptor, and STAT4 Drives Sustained Fibroblast Production of Inflammatory Mediators

Abstract: SUMMARY Fibroblasts are major contributors to and regulators of inflammation and dominant producers of interleukin-6 (IL-6) in inflammatory diseases like rheumatoid arthritis. Yet, compared to leukocytes, the regulation of inflammatory pathways in fibroblasts is largely unknown. Here, we report that analyses of genes coordinately upregulated with IL-6 pointed to STAT4 and leukemia inhibitory factor (LIF) as potentially linked. Gene silencing revealed that STAT4 was required for IL-6 transcription. STAT4 was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 57 publications
3
124
0
1
Order By: Relevance
“…The induction of GM‐CSF production in T cells involves the activation of both NF‐κB and NFAT2 . The activation of NF‐κB pathway was also reported in TNF‐α‐ and IL‐17A‐induced activation of synovial fibroblasts and endothelial cells . In our study, we revealed that the same synergistic activation of NF‐κB and NFAT2 promoted IL‐17A‐induced GM‐CSF production in Sca‐1 + cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…The induction of GM‐CSF production in T cells involves the activation of both NF‐κB and NFAT2 . The activation of NF‐κB pathway was also reported in TNF‐α‐ and IL‐17A‐induced activation of synovial fibroblasts and endothelial cells . In our study, we revealed that the same synergistic activation of NF‐κB and NFAT2 promoted IL‐17A‐induced GM‐CSF production in Sca‐1 + cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…Although it does not affect STAT3, LIF can activate STAT1 in many different cell types (Durbin et al, 1996;Fujio et al, 1997;Jenab & Morris, 1998). Until recently, Brenner's group reported that LIF expression is elevated in both human and mouse models of arthritis and drives the transcription and activation of STAT4 in fibroblasts, leading to the sustained release of inflammatory mediators, including IL6, IL-1b, and IL-11 (Nguyen et al, 2017). This group demonstrated that LIFR and STAT4 form a molecular complex with the JAK1 and TYK2 kinases, controlling STAT4 activation and binding to the Il6 promoter in TNF-and IL-17-treated fibroblasts, which in turn maintains fibroblast-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…"SPXX Repeats" dissociate STAT4 from LIFR for activation To investigate the means by which LIF activates STAT4 in CD4 + T cells, we pretreated CD4 + T cells with the JAK2 inhibitor LY2784544, which abolished the induction of STAT4 tyrosine phosphorylation by LIF in CD4 + T cells ( Fig 4A), indicating that STAT4 activation by LIF occurred via canonical JAK-STAT activation. Brenner's group recently reported that in human fibroblasts, LIF promoted STAT4 activation via LIFR in an autocrine manner (Nguyen et al, 2017). Furthermore, gp130 is implicated in STAT4 activation during IL-35 signaling (Collison et al, 2012).…”
mentioning
confidence: 99%
“…Thus, because of a desialylated glycome, galectin-3 could induce secretion of inflammatory mediators such as IL-6 or Ccl2 in SFs, increasing local concentrations of TNFα that would further reduce ST6Gal-1 and α2-6 sialylation, establishing an autocrine pro-inflammatory loop that could explain perpetuation of disease in a similar fashion shown by members of the IL6 family 43 . By contrast, healthy synovium shows higher levels of α2-6-Sialylation in SFs, perhaps masking LacNAc repeats and preventing inflammatory actions of galectins.…”
Section: Discussionmentioning
confidence: 98%